Pengaruh Label Halal, Kesadaran Halal, Dan Religiosity Terhadap Keputusan Pembelian Makanan Instan Korea Melalui Minat Beli (Studi Kasus Konsumen Gen Z Muslim/ah) - Makhfiyyani, Kanzani; Maura, Meidyna Syafa; Hidayatullah, Maulana Syarif (Jurnal Cendekia Manajemen (JCM); Vol 3 No 2 (2025): July, 2025)
The purpose of this research is to determine the influence of the Halal Label, Halal Awareness, and Religiosity on Korean Instant Food Purchasing Decisions through Purchase Intention. The research used quantitative methods with purposive sampling techniques, with a total of 160 samples. Hypothesis testing uses path analysis techniques processed with the SmartPLS 4.0 program. The research results show that the Halal Label directly influences Interest and Halal Awareness and Religiosity does not directly influence Interest. Halal Label, Halal Awareness, and Religiosity directly influence purchasing decisions. Interests have an influence on purchasing decisions. Apart from that, indirectly the Halal Label, through Interest, influences Purchasing Decisions, while for Halal Awareness and Religiosity through Interest, both SmartPLS calculations and the Sobel Test have no influence on Purchasing Decisions.